Stress related growth after severe trauma: Investigating long-term psychiatric outcomes and coping mechanisms 20+ years after injury. (28th May 2021) - Kalbas, Y; Halvachizadeh, S; Luidl, A T; Zelle, B; Pfeifer, R; Pape, H -C
Abstract: Objective: There is limited research on the long-term psychiatric outcomes of severely injured patients. Those studies existing, focus on the negativ effects like post-traumatic stress disorder, anxiety and depression. Yet, also psychiatric improvements can be noticed in patients after severe trauma, mainly focused on stress related growth. In our study we investigated coping mechanisms in multiply injured patients at least 20 years after trauma. Methods: 631 patients, who suffered a severe injury between 1971 and 1990 were contacted 20 or more years later. All patients were 3 to 60 years of age when injured and were attended to at the same institution. 36 questions inspired by the stress related growth scale (SRGS) and the post-traumatic growth inventory (PGI) were enquired via a questionnaire. Questions touched on 5 specific topics relating to growth: 1) relationships to others, 2) personal strengths, 3) appreciation of life, 4) new possibilities and 5) spiritual change. Each question quantified improvements in specific areas: Possible answers were „None at all", „some" and „a great deal". Results: A total of 338 patients returned the questionnaire and could be included in our study. Gender distribution was 114 females (33, 8%) to 223 males (66, 8%). 96, 5% of patients reported improvements regarding at least one of the 36 questions. Approximately a third of patients noticed distinct improvements regarding their relationship to others (29, 2%) and their appreciation of life (36, 2%). Furthermore, 32, 5% of patients registered overall positive attitudes towards new possibilities. Referring to spiritual changes, only 20, 5% of patients reported positive changes, while 55, 7% reported no changes at all. Regarding personal strengths, 23, 4% indicated overall positive changes compared with 35% indicating no changes at all. Statistical analysis showed women to adapt significantly better (p < 0, 01) in every aspect besides spiritual changes. Furthermore, we noticed weak positive correlations between positive changes and age at injury (r = 0.26) as well as injury severity (r = 0.152). We saw, however no correlation with general health. Conclusion: 20 years after severe trauma, patients report improvements in their relationship with others, appreciation of life and attitude towards new possibilities. Such coping mechanisms, as results of stress related growth, should be identified and fostered in clinical practice.